Fat Mass and Obesity Association gene Polymorphism in PCOS Iraqi Women (Baghdad Science Journal, 2020)
Polycystic syndrome (PCOS) is a considerable infertility disorder in adolescents and adult women in reproductive age. Obesity is a vigorous risk factor related to POCS. This study aims to evaluate the association of obesity and PCOS by investigating several parameters including: anthropological, biochemical (lipid profile, fasting blood sugar, glucose tolerance test, and hormone levels (LH, FSH, LH/FSH ratio, Estradiol2 and Testosterone),and genetic parameters (Fat mass and Obesity associated gene (FTO) polymorphism at rs17817449) in 63 obese and non-obese PCOS women. The biochemical tests were investigated by colorimetric methods while FTO gene polymorphism was detected by PCR–RFLP. Lipid profile, FBS, GTT, hormones (LH, LH/FSH ratio) in obese PCOS patients were significantly higher than non-obese non PCOS patients. It was found that the FTO variant TT risk genotype is a predisposing factor to obesity but not for PCOS. The study substantiated a possible familial risk factor for developing obesity among women in the same family.